Examining linguistic landscape through shop signs: drawing insights about language identity in Tamparuli Town - Daron Benjamin Loo (ResearchGate, 2022)
Examining the linguistic landscape (LL) of a particular locality can potentially offer rich sociolinguistic information. This may include aspects of ethnic identity associated with uses of language. A common source of LL information is from shop signs. In the context of Malaysia, LL studies have typically been conducted in major urban areas, with minimal information on the suburbs or rural areas. To address this gap, this presentation offers an examination of the LL of Tamparuli, a small town located on the west coast of Sabah with a large population of the Dusun ethnic group. A mixed-methods approach was employed, where quantitative data comprised the descriptive analysis of shop signs, and qualitative data derived from interviews with local informants who had lived in the area for over 60 years. There were 143 shop signs included in this study, all of which were found in the main shop blocks. The descriptive analysis found many shop signs in English (48.3%), which commonly contained a concept or proper name, followed by English nouns referring to commerce or services. This is followed by shop signs in Bahasa Melayu (BM) at 15.4%. There were also signs multilingual signs, where a combination of all or either English, BM or Mandarin Chinese was used. While English seemed to be a dominant language used in the signs, it does not signify the pervasive use of the language within the town community; instead, what is observed is the borrowing of lexical items. Based on the informants’ interview, this linguistic phenomenon may be recent, given that in the past, shop signs were typically meaningful phrases or names that were transliterated into BM, and modified by nouns such as kedai (shop) or restoran (restaurant). Based on these observations, the language identity of the town remains predominantly BM.